POLA PEMBERIAN MAKAN, PEMBERIAN ASI EKSKLUSIF, ASUPAN PROTEIN DAN ENERGI, SEBAGAI PENYEBAB STUNTING DI DESA GROGOL PONOROGO - Ratih Dwilestari Puji Utami (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2020)
Malnutrition is one of the problems related to child growth that has not been resolved until now, such of stunting. Stunting is a condition in which the child's growth, especially height or body length, has z-score less than -2 SD. The purpose of this study to identify the causes of stunting in children under five in Grogol village using a cross-sectional quantitative study approach. 67 samples through stratified random sampling and filling questionnaire. The analysis showed that there was a relationship between the incidence of stunting with feeding pattern (p = 0.001), protein intake (p = 0.001), history of exclusive breastfeeding (p = 0.002), and energy intake (p = 0.003). The conclusion of this study, feeding pattern has the strongest relationship with the incidence of stunting and very short stunting in toddlers.